SLIDING MODE CONTROLLER DESIGN: STABILITY ANALYSIS AND TRACKING CONTROL FOR FLEXIBLE JOINT MANIPULATOR (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2021)
Flexible robots are subject of many research-works since their advantages in terms of safety, compliance, low energy consumption, manoeuvrability, high payload to manipulator weight ratio, low cost, and high speed. However, the flexibility of manipulator’s links or joints and the under-actuation leads to complexity in the modelling and control. To deal with this problem, a sliding mode control is designed and applied to a presented model of the system. So, this paper presents the modelling of flexible joint manipulator, the design of adequate sliding mode controller which can stabilize the flexible joint manipulator. The robust tracking performance will be proved in the simulation.
Keywords: Sliding mode control; Flexible joint manipulator; Lyapunov stability theory; Hurwitz conditions; Trajectory tracking